Success Factors in Adopting AI in HRM: Perspective From the Private Sector in UAE - BETTAYEB, ABDERRAHMANE (2024)
Artificial intelligence (AI) is emerging as a transformative force in technological advancement, impacting the success of diverse business sectors. However, research on the specific success factors in AI adoption, especially in human resource management (HRM), remains limited. Previous studies have predominantly focused on AI techniques and applications within IT and industrial sectors rather than the HR context and primarily address applications like recruitment rather than exploring broader HR functions. This study aims to address these gaps by identifying key success factors for AI integration in HR across various applications, with a specific focus on the private sector in the United Arab Emirates (UAE), an area largely unexplored in existing literature. This research uses the Technology, Organisation, and Environment (TOE) framework combined with the Diffusion of Innovation (DOI) theory to investigate how these success factors influence AI adoption in HRM. Adopting a quantitative methodology, surveys were administered across UAE private firms to examine variables including factors under the Innovation feature of AI such as compatibility, relative advantage, complexity, trialability, and observability. Internal factors, such as top management support, organizational readiness and technical capability, and managerial capabilities along with external factors like government regulations and pressure, competitive pressure, Market status, and vendor partnerships, were also considered. Data analysis was conducted using SPSS and AMOS, employing tests such as Common Method Bias (CMB), Exploratory and Confirmatory Factor Analysis (EFA and CFA), and Structural Equation Modelling (SEM). This study provides insights into effective resource allocation for HR leaders considering AI adoption, offering implications for both theory and practice. The findings address key research questions, outline practical recommendations, and suggest avenues for future research to bridge existing literature gaps. Ultimately, this research will offer HR leaders in UAE private firms a framework to better understand and overcome AI adoption challenges, enabling informed decision-making and enhancing the strategic use of AI across HR functions and practices. Keywords: AI adoption, human resource management, Diffusion of Innovation Theory (DOI), Technology Organization and Environment Theory (TOE), Success factors, UAE private sector, Innovation feature of AI, Internal effect, External effect, and SPSS AMOS.